Dynamic Changes in Cognitive Function in Patients With Radiation-Induced Temporal Lobe Necrosis After IMRT for Nasopharyngeal Cancer - Liu, PeiYao; Niu, XiaoShuang; Ou, Dan; Qiu, JianJian; Lou, PengRong; Xue, LiangJun; Zhou, Xin; Xu, Tingting; Wang, XiaoShen (Frontiers in Oncology, 2020)
Abstracts Purpose: Radiation-induced temporal lobe necrosis (TLN) was once regarded as a progressive and irreversible disease in the era of two-dimensional radiotherapy. However, in the era of intensity-modulated radiotherapy (IMRT), the long-term development process of TLN remains unknown. We performed a prospective study to evaluate the dynamic changes in cognitive function in patients with TLN after definitive IMRT for nasopharyngeal carcinoma (NPC). Methods and Patients: The enrollment criteria were as follows: ①Patients must have had confirmed NPC and must have received only one course of definitive IMRT. ②Patients radiologically diagnosed with TLN during follow-up. ③Patients with TLN who had not undergone surgical resection. ④Patients with TLN with a follow-up period of more than 2 years. Cognitive function was measured with the mini-mental state examination (MMSE) at an interval of every 3 months. Changes in the size of the necrotic mass in the temporal lobe were evaluated by magnetic resonance imaging (MRI). The treatment interventions included the wait and see policy or the administration of nerve growth factor (NGF) combined with pulsed steroids. Results: From January 2008 to December 2017, 86 patients with TLN entered this study. With a median follow-up of 32 months (26-50 months), 60 patients (70%) showed normal cognitive function as quantified by MMSE scores (≥27). Twenty-six patients (30%) demonstrated obvious cognitive impairment (MMSE scores ≤26) during follow-up. However, after receiving NGF combined with pulsed steroids, cognitive function improved significantly, and 21 out of 26 patients demonstrated recovery to normal levels. MRI studies demonstrated that 10 patients had a complete response (CR), 13 had a partial response (PR), and 3 had stable disease (SD). Conclusions: In the IMRT era, TLN is not always a progressive disease. Most patients remain stable both in terms of their cognitive function and in the size of the necrotic mass. For patients with progressive TLN, active intervention with the administration of nerve growth factor and pulsed steroids can not only improve cognitive function but also decrease the size of the necrotic mass.